2021
DOI: 10.3389/fnut.2021.667622
|View full text |Cite
|
Sign up to set email alerts
|

Lipidomic and Transcriptomic Analysis of the Longissimus Muscle of Luchuan and Duroc Pigs

Abstract: Meat is an essential food, and pork is the largest consumer meat product in China and the world. Intramuscular fat has always been the basis for people to select and judge meat products. Therefore, we selected the Duroc, a western lean pig breed, and the Luchuan, a Chinese obese pig breed, as models, and used the longissimus dorsi muscle for lipidomics testing and transcriptomics sequencing. The purpose of the study was to determine the differences in intramuscular fat between the two breeds and identify the r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
28
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(33 citation statements)
references
References 38 publications
(36 reference statements)
3
28
2
Order By: Relevance
“…In the present study, the difference between IMF and VAT at the lipid molecular level was mainly manifested in GPs (PC, PE, LPE, PG, PI, PS) and GLs (DG and TG), with IMF rich in GPs and VAT rich in GLs. This result was consistent with a previous report, which showed that the LDM of pigs contains a large GP content and upregulated PUFAs ( 29 ). The heterogeneity of lipid profiles in IMF and VAT could be associated with cell type and fat deposition rates ( 30 ).…”
Section: Discussionsupporting
confidence: 94%
See 2 more Smart Citations
“…In the present study, the difference between IMF and VAT at the lipid molecular level was mainly manifested in GPs (PC, PE, LPE, PG, PI, PS) and GLs (DG and TG), with IMF rich in GPs and VAT rich in GLs. This result was consistent with a previous report, which showed that the LDM of pigs contains a large GP content and upregulated PUFAs ( 29 ). The heterogeneity of lipid profiles in IMF and VAT could be associated with cell type and fat deposition rates ( 30 ).…”
Section: Discussionsupporting
confidence: 94%
“…According to the degree of impact on the metabolic pathway, GL and GP metabolisms were key metabolic pathways regulating lipid deposition. This result was similar to the findings reported for IMF deposition in pork ( 29 ). This was further supported by the GLs and GPs of significantly different lipids being mostly synthesized by the TG and GP pathways ( 9 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…With the improvement of people's living standards, meat of increasingly high quality is pursued, and the meat from Duroc and other lean pigs can no longer meet the people's needs. Previous researchers have found that meat quality was related to muscle fiber characteristics and intramuscular fat content ( 3 , 4 ). The character of muscle fiber is an important factor affecting meat quality ( 5 , 6 ).…”
Section: Introductionmentioning
confidence: 99%
“…Such data indicate that lipid species can be used for the differentiation of the meat quality of different pork samples, facilitating the determination of the geographical origin of meat. Zhang et al (2021b) performed lipidomics (UPLC-ESI-MS/MS) and transcriptomics analysis of the muscle of different breeds of pigs to reveal differences in intramuscular fat (IMF), and they found that Luchuan pigs showed significantly higher IMF content than Duroc pigs. Further, a total of 605 lipids were detected in 23 categories, including 211 TG, 95 PCs, 66 PEs, 46 DG, and 37 Cer.…”
Section: Application Of Lipidomics To Assess Food From Farm Animalsmentioning
confidence: 99%